Association of Serum Uric Acid and Liver Enzymes in Adults at Tertiary Level Hospital in Bangladesh (Bangladesh Medical Journal, 2024)
The level of serum uric acid (SUA) has been linked to metabolic syndrome, diabetes, and cardiovascular disease. The purpose of this study was to evaluate the relationship between SUA and serum liver enzymes in a Bangladeshi adult population. This cross-sectional study was conducted among apparently healthy adults aged >18 years, from March 2019 to February 2020 at the Department of Biochemistry, Sir Salimullah Medical College (SSMC), Dhaka. SUA, liver enzymes, lipid profile and other biochemical markers were measured in the collected samples by using standard methods. All statistical analyses were performed by using SPSS version 22.0 software and p